Pseudorapidity densities of charged particles with transverse momentum thresholds in pp collisions at s =5.02 and 13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2023)
The pseudorapidity density of charged particles with minimum transverse momentum (${p}_{\mathrm{T}}$) thresholds of 0.15, 0.5, 1, and $2\text{ }\text{ }\mathrm{GeV}/c$ is measured in pp collisions at the center of mass energies of $\sqrt{s}=5.02$ and 13 TeV with the ALICE detector. The study is carried out for inelastic collisions with at least one primary charged particle having a pseudorapidity ($\ensuremath{\eta}$) within $\ifmmode\pm\else\textpm\fi{}0.8$ and ${p}_{\mathrm{T}}$ larger than the corresponding threshold. In addition, measurements without ${p}_{\mathrm{T}}$-thresholds are performed for inelastic and nonsingle-diffractive events as well as for inelastic events with at least one charged particle having $|\ensuremath{\eta}|<1$ in pp collisions at $\sqrt{s}=5.02\text{ }\text{ }\mathrm{TeV}$ for the first time at the LHC. These measurements are compared to the pythia 6, pythia 8, and epos-lhc models. In general, the models describe the $\ensuremath{\eta}$ dependence of particle production well. However, discrepancies are observed for the highest transverse momentum threshold (${p}_{\mathrm{T}}>2\text{ }\text{ }\mathrm{GeV}/c$), highlighting the importance of such measurements for tuning event generators. The new measurements agree within uncertainties with results from the ATLAS and CMS experiments obtained at $\sqrt{s}=13\text{ }\text{ }\mathrm{TeV}$.
Keywords: Pseudorapidity; Physics; Charged particle; Nuclear physics; Large Hadron Collider; Particle physics; Transverse plane; Ion; https://purl.org/pe-repo/ocde/ford#1.03.03